The Intriguing Link between the Intestinal Microbiota and Cardiovascular Disease - Lippi, Giuseppe; Danese, Elisa; Mattiuzzi, Camilla; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2017)
Human microbiota is a term conventionally used to define the normal flora of microbes living in all of us, most of which are resident in the gastrointestinal tract. Despite it having been known for some time that the vast majority of intestinal bacteria exert a strong influence on human life, recent technologic breakthroughs have made it possible to more accurately characterize the host microbial communities and explore their relationship with many human diseases. Notably, the evidence accumulated over the past 10 years suggests that a reasonable relationship can now be established between gut microbiota composition and the risk of cardiovascular disease. The most convincing information comes from data generated by studies involving trimethylamine-N-oxide (TMAO)-producing bacteria. It seems now clear that these bacterial strains may actively contribute to increase the concentration of endogenous TMAO and consequently enhance the risk of ischemic and thrombotic disorders, so opening intriguing scenarios for effective prevention of cardiovascular disease by targeting the intestine by means of diet, probiotics, prebiotics, antibiotics, or even transplantation of gut microbes.
Keywords: intestine; gut; microbiota; microbiome; cardiovascular disease